Composition of the Catch of 28 GT Boat Bagan in Carocok Tarusan Waters, Pesisir Selatan District West Sumatra Province - Afriadi, Ahmad; Mairizal, Mairizal; Magwa, Rizky Janatul; Alwi, Yun; Lisna, Lisna; Ramadan, Fauzan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
The waters of West Sumatra are one of the richest in Indonesia, and they have potential in the fisheries sector. They use various types of fishing gear, one of which is boat bagan. One of the most common fishing tools in fishing ports is the boat bagan in the waters of Carocok Tarusan, West Sumatra. The catches usually caught by boats are anchovies and tuna. The research aims to determine boat bagan composition in Carocok Tarusan Waters, Pesisir Selatan Regency, West Sumatra Province. This research was carried out on 20 July – 20 August 2023. The method used in this research was a survey method, with direct observations in the field and conducting interviews with fishermen. The tools used in this research were scales, a logbook, a cellphone camera, a ruler, a fishfinder, and a refractometer. The materials used are catches from bagan boats. The data is then calculated and differentiated between main catch, bycatch, and discard. The results of this research show that the composition of the main catch of boat charts is anchovies (Stolephorus spp) as much as 875 kg (24.7%) and tuna (Euthynnus affinis) 888 kg (25%). At the same time, fish that are bycatch consists of several types of fish, namely, trevally (Selaroides leptolepis) as much as 248 kg (7%), peperek (Aurigequula fasciata) as much as 710 kg (20%), mackerel (Rastrelliger sp) as much as 457 kg (12.9%), squid (Loligo sp) as much as 104 kg (2.93%), and mackerel scad (Decapterus) as much as 267 kg (7.5%), for the discarded catch, namely pufferfish (Tetraodontidae) as much as 0.25 kg (0.01 %). The discard catch consists of pufferfish